Peningkatan Mutu Lembaga Pendidikan Dasar Melalui Manajemen Sarana dan Prasarana - Wahyu Purwasih; Ahmad Sahnan (Program Studi PGSD Universitas Madako Tolitoli, 2022)
This paper presents the management of basic education facilities and infrastructure. The management functions of basic education infrastructure include planning, procurement, distribution, maintenance, deletion, and supervision. There are several things that must be considered during the implementation of infrastructure management, such as the number of children, school conditions, input from student parents, as well as developments in science and technology. With the implementation of optimal basic education infrastructure management, it is expected that the quality of education services can increase and the resulting output can also match the vision and mission of the institution. The type of this research is descriptive qualitative research. The methods used are interviews, observation and documentation. Furthermore, the data collected was analyzed and conclusions were drawn. The results of the study show that Ar-Rafif Yogyakarta basic education has implemented facilities and infrastructure management which includes planning, procurement, recording, distribution, maintenance, and deletion. Management of infrastructure facilities is carried out by the school principal with supervision from the school director. In addition to procuring adequate learning media, Ar Rafif Yogyakarta basic education also has a library room, so it can better support learning activities.